Analisis Pengaruh Investasi, TPT dan UMR terhadap Kemiskinan di Provinsi Sumatera Barat Tahun 2010-2024 - Rinaldi Rinaldi; Joko Suharianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Poverty has become a quite burdensome economic challenge for developing countries. In addition, poverty is also closely linked to inequality. In Indonesia, poverty is one of the economic challenges that is difficult to face to date. This study examines the effect of Investment, TPT and UMR on poverty in West Sumatra in 2010-2024. The data used are secondary time series data obtained through the BPS website. The analysis method used is the multiple regression analysis method using the E-views tool. The results of the study show that Investment has a significant negative effect on poverty, the Open Unemployment Rate has a positive effect, but is not significant on poverty, and UMR has a significant negative effect on poverty. Simultaneously, these three variables have a significant effect on poverty.